2016
DOI: 10.1017/s1047951115002723
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cardiac surgery in patients with trisomy 18: a single-institutional experience

Abstract: Cardiac surgery was effective in prolonging survival by managing high pulmonary blood flow; however, the indication for surgery should be carefully considered on a case-by-case basis, because the risk of sudden death remains even after surgery. Patients' families should be provided with sufficient information to make decisions that will optimise the quality of life for both patients and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Medical care for children with life-limiting conditions should be individualized and consistent with the values of the parents. 5,1120 Clinicians should communicate the heterogeneous nature of T13-18, as well as the uncertainty associated with the benefits and risks of interventions. Interactions with parents to make these decisions are complex.…”
Section: Discussionmentioning
confidence: 99%
“…Medical care for children with life-limiting conditions should be individualized and consistent with the values of the parents. 5,1120 Clinicians should communicate the heterogeneous nature of T13-18, as well as the uncertainty associated with the benefits and risks of interventions. Interactions with parents to make these decisions are complex.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, cardiac surgery including palliative procedures (pulmonary artery banding, ductus ligation) and intracardiac repair (closure of ventricular septal defect in most) was performed safely and seemed to contribute to longer survival in children with trisomy 18 or trisomy 13. This was demonstrated in a cohort of the multicenter Pediatric Cardiac Care Consortium in US [Graham et al, ]; in a tertiary medical center in Japan, the Japanese Red Cross Medical Center [Kaneko et al, , ; Kobayashi et al, ]; in a tertiary medical center in Japan, Kyushu Koseinenkin Hospital [Muneuchi et al, ]; in a multicenter registry of the Japanese Society of Pediatric Cardiology and Cardiac Surgery [Maeda et al, ]; in a tertiary medical center in Washington, DC, Children's National Health System [Costello et al, ]; in the Tracking Rare Incidence Syndromes (TRIS) project [Bruns and Martinez, ]; and in a tertiary medical center in Japan, Nagoya City University Hospital [Nakai et al, ].…”
mentioning
confidence: 99%
“…Studies from Japan also reported improved survival in trisomy 18 infants with congenital heart defects, if provided with intensive cardiac management including pharmacologic ductal intervention as well as cardiac surgery. [15][16][17] In our series, there were five infants with ductal-dependent congenital heart diseases. All the five infants received prostaglandin E1 infusions and one underwent cardiac surgery.…”
Section: Discussionmentioning
confidence: 87%